Comparison of a New Video Intubation Stylet and McGrath® MAC Video Laryngoscope for Intubation in an Airway Manikin with Normal Airway and Cervical Spine Immobilization Scenarios by Novice Personnel: A Randomized Crossover Study. (10th November 2021) - Park, Jin-Woo; An, Sungmin; Park, Seongjoo; Nahm, Francis Sahngun; Han, Sung-Hee; Kim, Jin-Hee
Abstract : The use of both a video laryngoscope and a video intubation stylet, compared with the use of a direct laryngoscope, is not only easier to learn but also associated with a higher success rate in performing endotracheal intubation for novice users. However, data comparing the two video devices used by novice personnel are rarely found in literature. Nondelayed intubation is an important condition to determine the prognosis in critically ill patients; hence, exploring intubation performance in various situations is of clinical significance. This study is aimed at comparing a video stylet and a video laryngoscope for intubation in an airway manikin with normal airway and cervical spine immobilization scenarios by novice personnel. We compared the performance of intubation by novices between the Aram Video Stylet and the McGrath® MAC video laryngoscope in an airway manikin. Thirty medical doctors with minimal experience of endotracheal intubation attempted intubation on a manikin five times with each device in each setting (normal airway and cervical spine immobilization scenarios). The order of use of the devices in each scenario was randomized for each participant. In the normal airway scenario, the Aram stylet showed a significantly higher rate of successful intubation than the McGrath® (98.7% vs. 92.0%; odds ratio (95% CI): 6.4 (1.4–29.3); p = 0.006 ). The intubation time was shorter using the Aram Stylet than that using the McGrath® video laryngoscope (p < 0.001 ). In the cervical immobilization scenario, successful endotracheal intubation was also more frequent using the Aram stylet than with the McGrath® (96.0% vs. 87.3%; odds ratio (95% CI): 3.5 (1.3–9.0); p = 0.007 ). The Aram Stylet intubation time was shorter (p < 0.001 ). In novice personnel, endotracheal intubation appears to be more successful and faster using the Aram Video Stylet than the McGrath® MAC video laryngoscope.